Transition Metal Oxide Anodes for Electrochemical Energy Storage in Lithium‐ and Sodium‐Ion Batteries. Issue 1 (18th November 2019) - Fang, Shan; Bresser, Dominic; Passerini, Stefano
Abstract: Lithium‐ion batteries (LIBs) with outstanding energy and power density have been extensively investigated in recent years, rendering them the most suitable energy storage technology for application in emerging markets such as electric vehicles and stationary storage. More recently, sodium, one of the most abundant elements on earth, exhibiting similar physicochemical properties as lithium, has been gaining increasing attention for the development of sodium‐ion batteries (SIBs) in order to address the concern about Li availability and cost—especially with regard to stationary applications for which size and volume of the battery are of less importance. Compared with traditional intercalation reactions, conversion reaction‐based transition metal oxides (TMOs) are prospective anode materials for rechargeable batteries thanks to their low cost and high gravimetric specific capacities. In this review, the recent progress and remaining challenges of conversion reactions for LIBs and SIBs are discussed, covering an overview about the different synthesis methods, morphological characteristics, as well as their electrochemical performance. Potential future research directions and a perspective toward the practical application of TMOs for electrochemical energy storage are also provided. Abstract : Transition metal oxides (TMOs) are considered to be alternative anode materials for advanced rechargeable batteries. This review focuses on the comparison of TMOs when used as electrode active materials in lithium‐ion batteries and sodium‐ion batteries, the current opportunities and future challenges, the research progress on the synthesis methods, morphological characteristics, and their electrochemical performance.